γδ T LYMPHOCYTES AS A FIRST LINE OF IMMUNE DEFENSE: OLD AND NEW WAYS OF ANTIGEN RECOGNITION AND IMPLICATIONS FOR CANCER IMMUNOTHERAPY. - Zocchi, Maria Raffaella; Poggi, Alessandro (Frontiers in Immunology, 2014)
Among γδT cells, the Vδ1 subset, resident in epithelial tissues, is implied in the defense against viruses, fungi and certain hematological malignancies, while the circulating Vδ2 subpopulation mainly respond to mycobacteria and solid tumors. Both subsets can be activated by stress-induced molecules (MIC-A, MIC-B, ULBPs) to produce pro-inflammatory cytokines and lytic enzymes and destroy bacteria or damaged cells. γδT lymphocytes can also recognize lipids, as those associated to M. tuberculosis, presented by the CD1 molecule, or phosphoantigens (P-Ag), either autologous, which accumulates in virus-infected cells, or microbial produced by prokaryotes and parasites. In cancer cells P-Ag accumulate due to alterations in the mevalonate pathway; recently, butyrophilin 3A1 has been shown to be the presenting molecule for P-Ag. Of interest, aminobisphosphonates indirectly activate Vδ2 T cells inducing the accumulation of P-Ag. Based on these data, γδT lymphocytes are attractive effectors for cancer immunotherapy. However, the results obtained in clinical trials so far have been disappointing: this review will focus on the possible reasons of this failure as well as on suggestions for implementation of the therapeutic strategies.